Evaluating Aftereffects of Short-Duration Transcranial Random Noise Stimulation on Cortical Excitability - Leila Chaieb; Walter Paulus; Andrea Antal (Neural Plasticity)
A 10-minute application of highfrequency (100–640 Hz) transcranial random noise stimulation (tRNS) over the primary motor cortex (M1) increases baseline levels of cortical excitability, lasting around 1 hr poststimulation Terney et al. (2008). We have extended previous work demonstrating this effect by decreasing the stimulation duration to 4, 5, and 6 minutes to assess whether a shorter duration of tRNS can also induce a change in cortical excitability. Single-pulse monophasic transcranial magnetic stimulation (TMS) was used to measure baseline levels of cortical excitability before and after tRNS. A 5- and 6-minute tRNS application induced a significant facilitation. 4-minute tRNS produced no significant aftereffects on corticospinal excitability. Plastic after effects after tRNS on corticospinal excitability require a minimal stimulation duration of 5 minutes. However, the duration of the aftereffect of 5-min tRNS is very short compared to previous studies using tRNS. Developing different transcranial stimulation techniques may be fundamental in understanding how excitatory and inhibitory networks in the human brain can be modulated and how each technique can be optimised for a controlled and effective application.